We have the following, L, of the beam varies as the product of the width and the square of the height:
![L\propto w\cdot h^2](https://img.qammunity.org/2023/formulas/mathematics/college/12rrdjtgnlp24mq76hm0j0x35p063sffjj.png)
And varies inversely as the lenght of the wooden beam:
![L\propto(w\cdot h^2)/(l)](https://img.qammunity.org/2023/formulas/mathematics/college/j524r9vikhk8epzaowrxv188m5lxgpkqr6.png)
therefore:
![L=k\cdot(w\cdot h^2)/(l)](https://img.qammunity.org/2023/formulas/mathematics/college/e1ixyuejqx4hay1615kq1tu6kbc7bb7ecr.png)
where k is the proportionality constant
w = 4, h=8, l = 216 and L = 5050
![\begin{gathered} 5050=k\cdot(4\cdot8^2)/(216) \\ k=(5050\cdot216)/(256) \\ k=4260.93 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/j3rux36ivlkpckebf5h9gtgfr13ozyp9of.png)
now, if w = 2, h = 5, l = 144:
![\begin{gathered} L=4260.93\cdot(2\cdot5^2)/(144) \\ L=1479.5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/s12zsmjtfkvawa6f791w9m490uzf6qy892.png)